KATEKIS PROFESIONAL DI TENGAH KONSTELASI MASYARAKAT EKONOMI ASEAN(MEA) - Keristian Dahurandi (STIPAS St. Sirilus Ruteng, 2016)
Now, we are in Asean Economic society. It means every man is demanded to improve him/herself, undergoing severe training as a competitive person in order to not be marginalized in MEA. Catehist as the part of society is also included in this insist. So, the catechists must perform theirself competitively and professionally. As a professional, chatechist must have the standard of expert and certain competency in running their profession.The consequences of prefession is contract of employment, namely doing the job in compliance with minimal demand rewarded and decided standard. Beside it, pastoral as a profession has etiher inside or outside competition. The outside competitions such as the the better capability and skill. Through this article, Christian Dahurandi presents the ideal concept about the ideal, professional and competitive chatechist in coping with MEA. At least, the writer suggests that in relation with inside competition, pastoral agent must competitive and creative in obtaining the job opportunity. The pastoral profession will face the global market context that current to free trade are in MEA asociation.